ANALSIS NILAI TAMBAH KERIPIK BUAH DI KECAMATAN TAMBANG KABUPATEN KAMPAR - Ermi Tety; Samsul Kamal (Program Studi Pendidikan Ekonomi Universitas Riau, 2016)
This research used descriptive analysis, cost and income analysis, business efficiency (RCR) analysis, and added value analysis with Hayami method. The result showed that pineapple chips and jackfruit chips agroindustrial business already profitable. An average of 12 businessman ear net income of pineapple chips and jackfruit chips each of Rp. 8.350.062,26 per month and Rp. 1.243.240,79 per month. The processing efficiency of pineapple and jackfruit into pineapple chips and jackfruit chips each of 1,37 dan 1,85. The added value for pineapple processing into pineapple chips is Rp. 2.389,30 with ratio of added value to production equal to 42,79% and added value for jackfruit processing into jackfruit chips is Rp. 15.575,51 with ratio of added value to production equal to 71,61%.